Atopic dermatitis and vitamin D - Inês Rodrigues; Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Atopic dermatitis (AD) results from the interaction between dysfunction of the skin barrier, dysregulation of the immune system, and alteration of the skin microbiome. As the most common inflammatory skin disease worldwide and still increasing, it is a real health problem. Vitamin D deficiency is also considered a global problem affecting 13 out of 100 people in Europe. Since vitamin D is involved in the formation of the epidermal barrier, by the synthesis of structural proteins and regulation of keratinocyte proliferation and differentiation, there is a rational to evaluate the relation between vitamin D levels and the prevention or treatment of AD. The authors performed a review of the existing scientific literature on the role of vitamin D in AD. Although studies are scarce not very robust with no consensual results, most studies report lower serum levels of vitamin D in patients with AD. In addition, there seems to be an inverse relationship between plasma levels of vitamin D and clinical severity, a hypothesis that is reinforced by studies that demonstrated a statistically significant benefit of vitamin D supplementation for improving clinical symptoms and signs of AD. Some studies also suggest a possible influence of prenatal vitamin D levels on the onset of AD during childhood. Therefore, vitamin D supplementation may play a relevant role as a complement to the treatment of AD or for its prevention, but more and better scientific evidence is needed to confirm this.